Impact of legislative solutions on counterfeiting of medicines at european level - Bechir, Elis; Erimia, Cristina-Luiza (Technium BioChemMed, 2023)
Counterfeit medicines pose a serious threat to health systems, industry and society. Globalization of commerce and the active online environment have significantly increased the health risks associated with counterfeiting medicines. Considering these alarming issues, the European Parliament and the Council have adopted a legislative framework aimed at combating the entry of falsified medicinal products into the legal supply chain, without affecting the functioning of the internal market for medicinal products for human use. This article aims to present the impact of the new legislative solutions known as the "Falsified Medicines Directive", by which, in 2011, the European Union took an imperative step in protecting public health, establishing the legal basis by which the falsification of medicines is a criminal law action, which deprives patients of safe and quality medical treatment.